Pendeteksian Kecurangan Laporan Keuangan dengan Beneish M-Score Pada perusahaan Manufaktur - Ariansyah Ariansyah; Yulia Yustikasari (Jurnal Pena-Mas Akuntansi, 2022)
This study aims to determine the percentage of manufacture listed on the BEI in 2016-2017 which are classified as non manipulator, gray company and manipulator by using five indexes of Days Sales in Receivable Index (DSRI), Gross Margin Index (GMI), Asset Quality Index (AQI), Sales Growth Index (SGI), and Total Accrual To Total Assets Index (TATA). The method of collecting data is documentation with the number of samples are 54 manufacture companies listed on BEI Year 2016-2017. Data analysis used is Beneish Ratio Index. The results revealed that the percentage of manufacture companies classified as non manipulator in 2016-2017 amounted to 68.5%, . The percentage of manufacture companies classified as gray company in 2016-2017 amounted to 26% . Percentage of manufacture companies that are classified as manipulators In 2016-2017 amounted to 5.5%.